2007
DOI: 10.1007/s10620-006-9490-9
|View full text |Cite
|
Sign up to set email alerts
|

Which Has Superior Acid-Suppressive Effect, 10 Mg Omeprazole Once Daily or 20 Mg Famotidine Twice Daily? Effects of Single or Repeated Administration in Japanese Helicobacter Pylori-Negative CYP2C19 Extensive Metabolizers

Abstract: Low-dose omeprazole is superior to full-dose famotidine in maintenance therapy for gastroesophageal reflux disease, whereas "on-demand" famotidine is more effective for relief of episodes of heartburn. To explain this apparent discrepancy, intragastric pH was measured for 24-hr seven times in eight Japanese Helicobacter pylori-negative cytochrome P450 2C19 extensive metabolizers; on Days 1, 8, and 15 of repeated administration of 10 mg of omeprazole once daily and of 20 mg of famotidine twice daily and before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
1
5
0
1
Order By: Relevance
“…As depicted in Figure 1, the mean percentage of time gastric pH > 4 was at its highest level on dosing day 1 for both doses of famotidine, then decreased on subsequent days of continued dosing, consistent with H2RA tachyphylaxis reported previously with prescription doses [20,[22][23][24] . A similar loss of H2RA antisecretory effect has been reported in other studies examining OTC doses of famotidine (versus omeprazole; Table 1) [16,25] . In contrast to H2RAs, PPIs do not exhibit [41] , 2000 OL Ranitidine 150 mg QID 5 d 28 1, 5 Day 5 Komazawa et al [20] infusion was increased by 29% (P < 0.05) and heartburn pain was decreased by 20% (VAS score, P < 0.06) and 23% (Likert score, P < 0.02) compared with placebo.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…As depicted in Figure 1, the mean percentage of time gastric pH > 4 was at its highest level on dosing day 1 for both doses of famotidine, then decreased on subsequent days of continued dosing, consistent with H2RA tachyphylaxis reported previously with prescription doses [20,[22][23][24] . A similar loss of H2RA antisecretory effect has been reported in other studies examining OTC doses of famotidine (versus omeprazole; Table 1) [16,25] . In contrast to H2RAs, PPIs do not exhibit [41] , 2000 OL Ranitidine 150 mg QID 5 d 28 1, 5 Day 5 Komazawa et al [20] infusion was increased by 29% (P < 0.05) and heartburn pain was decreased by 20% (VAS score, P < 0.06) and 23% (Likert score, P < 0.02) compared with placebo.…”
Section: Resultssupporting
confidence: 83%
“…Other OTC strategies, such as a PPI, may be needed to optimize management of frequent heartburn. tachyphylaxis, but rather show similar efficacy to H2RAs on dosing day 1, then increase in effectiveness over several days before reaching a sustained plateau effect for the duration of dosing (Figure 1) [14][15][16]18,22,[25][26][27][28][29] . Tachyphylaxis to H2RAs does not appear to be progressive, as studies have typically demonstrated no further reduction in antisecretory effect after the initial loss of potency is detected [21][22][23] .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…OTC H 2 RAs are indicated for treatment of heartburn and prevention of heartburn associated with eating food or drinking beverages that cause heartburn. A single dose of an H 2 RA can be effective for relieving and/or preventing heartburn, but repeat dosing can lead to rapid development of tolerance (tachyphylaxis; Figure ; Bardhan et al., ; Fackler, Ours, Vaezi, & Richter, ; Fandricks, Lönroth, Pettersson, & Vakil, ; Furuta et al., ; Gillen & McColl, ; Hsu et al., ; Huang & Hunt, ; Hurlimann, Abbüh, Inauen, & Halter, ; Komazawa et al., ; Lanzon‐Miller et al., ; Merki et al, ; Merki & Wilder‐Smith, ; Miner, Allgood, & Grender, ; Nwokolo, Smith, Gavey Sawyerr, & Pounder, ; Ono et al., ; Shimatani et al., ; Wilder‐Smith & Merki, ).…”
Section: H2ra (Eg Cimetidine Famotidine Nizatidine Ranitidine)mentioning
confidence: 99%
“…Additionally, histamine H2 receptor antagonist (H2 blocker) is useful for the control of symptoms caused by acid reflux (Wada et al 2005). Both PPI and H2 blocker could inhibit acid reflux through reduction of intragastric acid (Miner et al 2003;Rohss et al 2004;Topaloglu et al 2004;Bersenas et al 2005;Shimatani et al 2007;Tolbert et al 2011). However, to the best of our knowledge, there have been no studies investigating the effects of PPI or a H2 blocker on taste cells and hypogeusia among patients with LPR.…”
Section: Introductionmentioning
confidence: 99%